Case report: Epstein-Barr virus and constrictive pericarditis-An unusual combination - Mario Panebianco; Eduard Limonjiani; Roberto Formigari; Veronica Bordonaro; Aurelio Secinaro; Enrico Cetrano; Adriano Carotti; Lorenzo Galletti; Sonia Albanese (Frontiers Media S.A., 2023)
Constrictive pericarditis is a chronic inflammatory process that can lead to heart failure if not diagnosed and treated correctly. Although Epstein-Barr virus (EBV)-related pericarditis is a very rare condition, it should still be considered for a differential diagnosis. We report the case of an 18-year-old male, who was surgically treated for constrictive pericarditis, in which in situ hybridization to Epstein-Barr virus-encoded RNA (EBER) probe of the excised pericardium led to the subsequent etiological diagnosis of chronic pericarditis caused by EBV.